Towards Competence-Based Learning Design Driven Remote and Virtual Labs Recommendations for Science Teachers - Zervas, P.; Sergis, S.; Sampson, Demetrios; Fyskilis, S. (Kluwer Academic Publishers, 2015)
Remote and virtual labs (RVLs) are widely used by science education teachers in their daily teaching practice. This has led to a plethora of RVLs that are offered with or without cost. In order to organise them and facilitate their search and findability, several RVL web-based repositories have been operated. As a result, a key open challenge is to design and implement recommender systems that support science teachers in finding and selecting appropriate RVLs based on core pedagogical elements of their learning designs and their own information and communication technology (ICT)-supported teaching competence profiles. In response to this challenge, we propose a recommender system for supporting learning design driven RVLs recommendations taking into consideration teachers’ profiling elements related to the ICT-supported teaching competences for using RVLs. To achieve this, we propose an instantiation of the UNESCO ICT competency framework for teachers for the context of using RVL and capitalise on our previously proposed metadata schema for describing RVLs, which includes core elements of a learning design and teachers’ required ICT-supported teaching competences. Our evaluation results based on a user study, highlight the high level of ranking accuracy of our proposed recommender system and support its capacity to facilitate science teachers in selecting appropriate RVLs.